Differences in the level of knowledge on the football basic technique at SSB BPM and SSB Matra - Muhammad Isyroq Izdiharuddin; Syamsuryadin; Bayu Noval Renaldi; Dicky Surya Wibowo; Bayu Jati Pranowo; Muhammad Rayen Tirtayasa; Hidayat, Aditya Fajar; Rizki Maulana; Ivan Esperanza Dedanka; Rizky Fauzy; Farros Afriza Dzaqi, (Jorpres (Jurnal Olahraga Prestasi), 2025)
This study aimed to examine the level of knowledge of basic football techniques among football school players at Bintang Putra Melati Football School and Matra Sleman Football School. This study used a quantitative descriptive design with a questionnaire survey method. The population consisted of 160 players from Bintang Putra Melati Football School and 120 players from Matra Sleman Football School. The sampling technique used purposive sampling with the following criteria: 1. players who had been registered at Bintang Putra Melati Football School and Matra Sleman Football School for six months, 2. players who had participated in the Askab Sleman competition with Bintang Putra Melati Football School and Matra Sleman Football School, and 3. players who were willing to become research samples. Based on these criteria, the sample consisted of 20 players from each football school, with a total of 40 players. The instrument used in this study was a questionnaire. The data analysis technique used quantitative descriptive analysis with five categories: very high, high, moderate, low, and very low. The results showed that the level of knowledge of basic football techniques at Bintang Putra Melati Football School was categorized as very high for 0 players or 0%, high for 0 players or 0%, moderate for 19 players or 95%, low for 0 players or 0%, and very low for 1 player or 5%. Meanwhile, the level of knowledge of basic football techniques at Matra Sleman Football School was categorized as very high for 0 players or 0%, high for 0 players or 0%, moderate for 17 players or 85%, low for 1 player or 5%, and very low for 2 players or 10%. These findings indicate that Bintang Putra Melati Football School had a better level of basic football technique knowledge than Matra Sleman Football School. Therefore, coaches are expected to strengthen their role in developing and improving players' knowledge of basic techniques and football skills, especially in the 12-year-old age category.